1999
DOI: 10.1073/pnas.96.26.15316
|View full text |Cite
|
Sign up to set email alerts
|

BAS1 : A gene regulating brassinosteroid levels and light responsiveness in Arabidopsis

Abstract: The Arabidopsis bas1-D mutation suppresses the long hypocotyl phenotype caused by mutations in the photoreceptor phytochrome B (phyB). The adult phenotype of bas1-D phyB-4 double mutants mimics that of brassinosteroid biosynthetic and response mutants. bas1-D phyB-4 has reduced levels of brassinosteroids and accumulates 26-hydroxybrassinolide in feeding experiments. The basis for the mutant phenotype is the enhanced expression of a cytochrome P450 (CYP72B1). bas1-D suppresses a phyB-null allele, but not a phyA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
312
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 352 publications
(334 citation statements)
references
References 55 publications
(46 reference statements)
15
312
0
2
Order By: Relevance
“…Some P450s catalyze oxidation steps in the biosynthetic pathway of plant sterols and BRs (Halkier, 1996;Chapple, 1998), whereas others catalyze hydroxylation or oxidation steps in the conversion from campesterol to BL. Yet another P450 protein, CYP72B1, inactivates BL through C26-hydroxylation (Neff et al, 1999). In zinnia cells, 3DT, 6-Deoxo3DT, and their downstream BRs completely reversed the uniconazole inhibition, whereas CT, TE, 6-DeoxoCT, 6-DeoxoTE, and 22-OHCR only partially overcame the uniconazole inhibition.…”
Section: -Deoxobrs Are As Active As 6-oxobrs In the Zinnia Systemmentioning
confidence: 99%
“…Some P450s catalyze oxidation steps in the biosynthetic pathway of plant sterols and BRs (Halkier, 1996;Chapple, 1998), whereas others catalyze hydroxylation or oxidation steps in the conversion from campesterol to BL. Yet another P450 protein, CYP72B1, inactivates BL through C26-hydroxylation (Neff et al, 1999). In zinnia cells, 3DT, 6-Deoxo3DT, and their downstream BRs completely reversed the uniconazole inhibition, whereas CT, TE, 6-DeoxoCT, 6-DeoxoTE, and 22-OHCR only partially overcame the uniconazole inhibition.…”
Section: -Deoxobrs Are As Active As 6-oxobrs In the Zinnia Systemmentioning
confidence: 99%
“…Among 37 P450 transcripts expressed higher in Col, 27 were expressed higher in Col flower tissue and 22 were expressed higher in Col leaf tissue, with 12 from these two datasets overlapping (five CYP71B subfamily members, CYP72A11, and the CYP72A12P pseudogene in its 3# UTR, CYP89A5, CYP97B3, CYP701A3, and CYP706A1). Of these 37 P450 transcripts, five code for defined biochemical functions with CYP88A3 and CYP701A3 being multifunctional kaurenoic and kaurene oxidases in GA synthesis (Helliwell et al, 1998(Helliwell et al, , 1999(Helliwell et al, , 2001), CYP83B1 mediating oxidations of indole-3-acetyldoxime in indole glucosinolate synthesis Naur et al, 2003), CYP707A2 mediating 8#-abscisic acid (ABA) hydroxylation in ABA degradation (Kushiro et al, 2004;Saito et al, 2004), and CYP734A1 mediating 26-hydroxylations on brassinolide and castasterone in brassinolide degradation (Neff et al, 1999;Turk et al, 2003). As to the 21 P450 transcripts expressed higher in the Ler ecotype, 12 were from flower tissue and 11 were from leaf tissue with two from these datasets overlapping (CYP74B2 and CYP83A1).…”
Section: Transcript Profiling In Col and Ler Ecotypesmentioning
confidence: 99%
“…In Arabidopsis, mutants overexpressing the BAS1/CYP734A1 and CHI2/ SHK1/SOB7/CYP72C1 genes were shown to reduce the level of active BRs (Neff et al, 1999;Nakamura et al, 2005;Takahashi et al, 2005). In vivo conversion assays revealed that CYP734A1 (formerly CYP72B1) converts castasterone and BL to biologically inactive C-26-hydroxylated products, while in the case of CYP72C1 inactivation of the same substrates is achieved by a different, yet unknown mechanism (Turk et al, 2003(Turk et al, , 2005.…”
mentioning
confidence: 99%